2015
DOI: 10.1089/wound.2014.0551
|View full text |Cite
|
Sign up to set email alerts
|

A Bilayer Engineered Skin Substitute for Wound Repair in an Irradiation-Impeded Healing Model on Rat

Abstract: Objective: An engineered skin substitute is produced to accelerate wound healing by increasing the mechanical strength of the skin wound via high production of collagen bundles. During the remodeling stage of wound healing, collagen deposition is the most important event. The collagen deposition process may be altered by nutritional deficiency, diabetes mellitus, microbial infection, or radiation exposure, leading to impaired healing. This study describes the fabrication of an engineered bilayer skin substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The challenge is seeding two cell lines to create a bilayer skin substitute as there needs to be a clear division between epidermal and dermal layers. After culturing scaffolds with adhered dermal cells, it is possible to seed epidermal cells dropwise on to one surface of the scaffold[214] or by placing the cellularized scaffold on to a surface previously adhered with keratinocytes[206]. Both of these techniques may create a bilayer scaffold, but one significant component is missing, the basement membrane.…”
Section: Creating Skin Substitutesmentioning
confidence: 99%
“…The challenge is seeding two cell lines to create a bilayer skin substitute as there needs to be a clear division between epidermal and dermal layers. After culturing scaffolds with adhered dermal cells, it is possible to seed epidermal cells dropwise on to one surface of the scaffold[214] or by placing the cellularized scaffold on to a surface previously adhered with keratinocytes[206]. Both of these techniques may create a bilayer scaffold, but one significant component is missing, the basement membrane.…”
Section: Creating Skin Substitutesmentioning
confidence: 99%
“…This supports previous findings that chitosan reduces the inflammatory response, therefore improving the inflammation stage. As a result, the greater proliferation and excellent collagen deposition during remodeling accelerate the wound healing process [ 50 ]. This biopolymer improves the wound tensile strength by speeding up the fibroblastic synthesis of collagen in the first few days of wound healing [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of chitosan also promotes the repair of damaged tissue, preventing infection of the wound [ 7 , 50 , 51 ]. This biopolymer increases the permeability of the inner and outer membranes and ultimately disrupts the bacterial cell membranes, releasing their contents.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from FSCs being used in combination with DPSCs, where a correct stratification, differentiation and well-ordered epithelia was observed 130 , Mohd Hilmi et al 132 reported that a chitosan-TESS composed of fibroblasts and FSCs serving as the epidermal component, was capable of restoring rat skin after radiation exposure by an increasing collagen bundle deposition.…”
Section: Human Stem Cells (Hsscs) In Tesssmentioning
confidence: 99%
“…Many different biomaterials have been investigated for the development of TESSs; from xenogeneic scaffolds such as porcine acellular matrix 130 , natural polymers like silk fibroin 159 , agarose 32 , 156 or chitosan 29 , 129 , 132 to substances that resemble in better way the native dermal components of skin: collagen 56 , 60 65 , 86 93 , 95 , 101 , 104 , 106 , plasma/fibrin 49 , 51 , 94 , 96 , 98 , 102 , 103 , hyaluronic acid 60 65 , 97 , elastin 56 , amniotic membrane 68 , 178 or extracellular matrix derived from fibroblasts 39 , 99 , 100 , 105 .…”
Section: Main Biomaterials For Clinical Tesssmentioning
confidence: 99%